Paradoxical Roles of Leucine-Rich α2-Glycoprotein-1 in Cell Death and Survival Modulated by Transforming Growth Factor-Beta 1 and Cytochrome c - Jemmerson, Ronald (Frontiers in Cell and Developmental Biology, 2021)
Leucine-rich α2-glycoprotein-1 (LRG1) has been shown to impact both apoptosis and cell survival, pleiotropic effects similar to one of its known ligands, transforming growth factor-beta 1 (TGF-β1). Recent studies have given insight into the TGF-β1 signaling pathways involved in LRG1-mediated death versus survival signaling, i.e., canonical or non-canonical. Interaction of LRG1 with another ligand, extracellular cytochrome c (Cyt c), promotes cell survival, at least for lymphocytes. LRG1 has been shown to bind Cyt c with high affinity, higher than it binds TGF-β1, making it sensitive to small changes in the level of extracellular Cyt c within a microenvironment that may arise from cell death. Evidence is presented here that LRG1 can bind TGF-β1 and Cyt c simultaneously, raising the possibility that the ternary complex may present a signaling module with the net effect of signaling, cell death versus survival, determined by the relative extent to which the LRG1 binding sites are occupied by these two ligands. A possible role for LRG1 should be considered in studies where extracellular effects of TGF-β1 and Cyt c have been observed in media supplemented with LRG1-containing serum.